A Systematic Review of Music Education, Acoustics, and STEAM Integration in South African Primary and Lower Secondary Schools - Yende, Sakhiseni Joseph (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This systematic review investigates the integration of music education with science, technology, engineering, arts, and mathematics (STEAM) in South African basic schools. The study explores how music instruction can enhance scientific and technological literacy, particularly through acoustics concepts and ICT-enabled digital tools. Peer-reviewed journal articles, policy documents, and case studies published between 2000 and 2025 were systematically analysed following established review guidelines, with 19 studies meeting the inclusion criteria. The findings reveal that although music is formally embedded within the national curriculum, its interdisciplinary potential for STEAM integration remains underutilised. Key challenges include limited teacher professional development, inadequate ICT infrastructure, curriculum constraints, and insufficient emphasis on scientific principles such as sound waves, frequency, resonance, and vibration. However, innovative practices including digital composition software, virtual acoustics simulations, music-mathematics integration activities, and collaborative cross-disciplinary projects demonstrate positive effects on learner engagement, conceptual understanding, creativity, and problem-solving skills. The review further indicates that structured integration of digital music skills can support inclusive participation and foster critical thinking across artistic and scientific domains. The study concludes that embedding scientific and technological concepts within music education can contribute significantly to holistic learner development and interdisciplinary competence. These findings have implications for curriculum design, teacher training programmes, resource allocation, and education policy, supporting the advancement of contextually responsive STEAM education in South African primary and lower secondary schools.
Keywords: Music education; STEAM integration; ICT in classrooms; Acoustic; South African basic schools